Unstable metaphors, uncertain minds: how metaphors shape judgments and opinions - Martina Montalti; Martina Montalti; Stefana Garello; Valentina Cuccio (Frontiers in Psychology)
IntroductionPrevious research has shown that experimentally manipulated physical states of instability negatively affect judgments and opinions. Based on this result, in the current study we want to investigate whether the processing of metaphorical expressions related to physical instability (e.g., “Our economy is shaky”) and underpinned by the conceptual metaphor EMOTIONAL STABILITY IS BALANCE negatively affects participants’ judgments.MethodsThree hundred participants were assigned to three experimental groups. Each group was presented with sentences containing, respectively, stable metaphors, unstable metaphors or unstable literal sentences. After reading the sentences, participants were asked to respond to six topical questions regarding current and future economic and life perspectives.ResultsData shows that across all six topical questions, reading stable metaphors led to more positive judgments compared to unstable sentences (both metaphors and literal ones). Moreover, in four questions out of six, reading unstable metaphorical sentences led to lower ratings compared to unstable literal sentences.DiscussionThese findings support the main claim of Conceptual Metaphor Theory, i.e., the idea that abstract and complex concepts are structured via metaphorical mappings from more concrete and simple ones and align with the Embodied Cognition Hypothesis. Furthermore, these findings suggest that metaphors can have a powerful influence on our perception of the world and contribute to our understanding of how metaphorical language can shape bodily experiences and attitudes.